Electrical Conductivity in Soil - Razak, Muhammad Naim; Che Ros, Ziana (Multidisciplinary Applied Research and Innovation, 2022)
Renewable energy is one of the methods to solve pollution problems. Pollutions leads to greenhouse effects, deforestation and thinner ozone layer. Indeed, the most important renewable sources of energy in Malaysia are biomass, wind, hydro, tidal, geothermal and solar. However, some of the sources are very difficult to be used as the renewable energy sources to produce electricity. Thus, in this project, a different conceptual approach is to be applied in order to generate certain amount of electricity. In this study, the relationship between, the physical of different types of soils, the level of effectiveness of soil moisture and also, the different types of pH values of the selected soils, and the amount of generated voltage level is evaluated . The methods involved in analyzing the relationship are described as follows. Firstly, choosing the types of soils required such are peat soil, clay and sand. Secondly, classified these soils into three conditions that are, dry, nor and wet. Thirdly, choosing copper (Cu) and zinc (Zn) material as an electrodes for electrical conductivity. All the components will be connected through crocodile clip wires so that the electric will flow. Lastly, the value for every data needed are recorded by using a digital multimeter. Apart from multimeter, the moisture tester tool also will be used to record the moisture of the soils from time to time. As the conclusion of this project, it is clearly stated that the type of soil used and their textures will influence the amount of current flow and the voltage gained throughout the study. It is also determined that different type of soils has different values of pH level which then produced different amount of electrical conductivity.